Efektivitas Penerapan CHSE (Cleanliness, Health, Safety, And Environment Sustainability) terhadap Kepuasan Pelanggan Menginap di Hotel Santika Premier Kota Malang - Pradiansah, Silvia Ajeng; Sugeha, Anisa Zuhria; 'Ulya, Ayu Fitriatul; Asrofi, Asrofi (University of Merdeka Malang, 2023)
Customer satisfaction while staying at a hotel is influenced by several things, at this time apart from service, there is also CHSE (Cleanliness, Health, Safety, And Environment Sustainability) which was implemented during the Covid-19 pandemic. This research was conducted with the aim of knowing the effectiveness of the application of CHSE (Cleanliness, Health, Safety, And Environment Sustainability) on customer satisfaction staying at Hotel Santika Premiere Malang City. The study used quantitative methods by distributing questionnaires and also observations to the Hotel Santika Premiere Malang City. After doing research, Cleanliness, Health, Safety, and Environmental Sustainability affect customer satisfaction by 60.2%, it can be concluded that Cleanliness(X1), Health(X2), Safety(X3), Environmental Sustainability(X4) stimulants have a significant effect. and positive on the variable Customer Satisfaction (Y). Customer satisfaction felt when visiting or staying at Hotel Santika Premiere Malang is a feeling of security and comfort when serviced by hotel employees